Oral cavity squamous cell carcinoma: impact of clear margin distance on locoregional control in patients undergoing postoperative radiotherapy - Uzun-Lang, Kristin; Held, Thomas; Freudlsperger, Christian; Plath, Karim; Hoffmann, Jürgen; Plinkert, Peter K.; Debus, Jürgen; Adeberg, Sebastian (Technology in cancer research & treatment, 2024)
Introduction - Postoperative radiotherapy can improve locoregional control (LC) in oral cavity squamous cell carcinoma (OCSCC) patients with positive resection margins. The present study aimed to evaluate the impact of surgical margin size on LC in this patient population. - Methods - This retrospective study involved 162 patients with OCSCC who underwent postoperative radiotherapy between 2000 and 2020 at the Department of Radiation Oncology, University Hospital Heidelberg and the German Cancer Research Center. The study aimed to determine the impact of different resection margins on LC, as well as overall survival (OS), progression-free survival (PFS), and treatment-related toxicity (CTCAE 4.03). - Results - Seventy-seven patients (47.5%) had involved (<1 mm) margins, 22 patients (13.6%) close (≤5 mm) margins, and 63 patients (38.9%) clear (>5 mm) margins. A surgical margin ≤ 5 mm was a significant predictor for worse LC (HR 2.6, 95% CI 1.2, 6.1), but not for OS (HR 1.2, CI 0.7, 1.9) or PFS (HR 1.2, 0.7, 2.0). - Conclusion - Patients who have narrow resection margins (1-5 mm) experience poor local control and should receive postoperative radiotherapy. It is necessary to conduct further prospective studies to determine whether a narrower margin window could be achieved to better determine the appropriate indication for adjuvant radiotherapy.